The Effect of Facial Tactics on Anxiety Levels in Postpartum Mothers - Dinengsih, Sri; Allen, Lesta; Kundaryanti, Rini (Jurnal MIDPRO, 2023)
The prevalence of mental disorders such as depression and anxiety disorders in mothers is recorded to have a weighted average of 15.6% during pregnancy and 19.8% after childbirth from around 14 million people from the Indonesian population, mothers experience anxiety after childbirth is recorded as much as 22.4%, anxiety in postpartum mothers that cannot be resolved can cause postpartum depression and other mental disorders that interfere with health. Knowing the effect of facial massage on the anxiety level of postpartum mothers in TPMB P West Jakarta in 2023. The study use quasi experimental type of research with pretest posstest with control two group research design, Taking sample done use technique total sampling amounted to 30 postpartum mother consisting of 15 responden group intervention and 15 responden  groups control. The instrument used was Hamilton Rate Scale- measurement questionnaire (HRS-A). data analysis use desriptive statistic and  paired T Test  to know difference level anxiety before and after intervention. The average value of the level of anxiety before facial massage (18.60) and after facial massage (13.30) and in the control group the results of the average value of the level of anxiety before the positive affirmations (17.27) and after the positive affirmations (16.13) with P-value of 0.000 < 0.05, means ada the effect facial massage on the level of anxiety in postpartum mothers. There is an effect of facial totok on anxiety levels in postpartum women. but facial totok is more significant in reducing anxiety levels than positive affirmations. for adding additional services and new entrepreneurs as complementary midwifery services by adding a facial totok treatment package along with the delivery package to overcome anxiety in postpartum women.